Structural characterisation, anticancer properties, and BSA binding of 2,6-dipyrazinylpyridines: Insights from experiment and theory - Enumula, Sreenivasulu; Shaikh, Javed; Shaikh, Amin; Sheikh, Kounsar N.; Tambe, Pranav; Lande, Dipali N.; Gejji, Shridhar P.; Shaligram, Parth; Gonnade, Rajesh; Bhadbhade, Mohan; Ahmed, Khursheed (Journal of Molecular Structure, 2026)
The phenyl-(2,6-di-2-pyrazinyl)pyridine derivatives (L1, L2) were synthesized using a one-pot Krohnke-type method, starting from 2-acetylpyrazine and substituted benzaldehydes. Their structures were characterized using a combination of spectroscopic (NMR, HRMS) and single-crystal X-ray diffraction techniques, complemented by density functional theory (DFT). Single-crystal X-ray diffraction reveals that L1 crystallizes in the C2/c space group (T = 296 K) with its supramolecular assembly being stabilized by C-H & ctdot;N and pi-pi stacking interactions, whereas L2 facilitates C-H & ctdot;N, N-H & ctdot;pi bifurcated, and pi-pi* interactions. The bio-interaction properties of L1 were studied using fluorescence spectroscopy with bovine serum albumin (BSA) as a model protein. Fluorescence studies demonstrated L1 induces static quenching of BSA, with a binding constant of 5.15 x 104 mol & sdot;dm-3. Synchronous and three-dimensional fluorescence spectra further demonstrated that L1 brings forth significant conformational changes in BSA. The compounds were evaluated for cytotoxicity against the HCT-116 human colorectal cancer cell line.
Keywords: 2; 6-dipyrazinylpyridines; Bovine serum albumin interaction; Cytotoxicity (HCT-116 cells); Density functional theory; Halogenated derivatives; Single-crystal X-ray diffraction